The effects of Gouqi extracts on Morris maze learning in the APP/PS1 double transgenic mouse model of Alzheimer’s disease - ZHANG, QIANLIN (D.A. Spandidos, 2013)
The present study examined the effects of Gouqi (Lycium barbarum) on the learning and memory abilities of an APP/PS1 double transgenic mouse model of Alzheimer’s disease. We employed a Morris water maze to examine the spatial memory in this mice line with or without Gouqi extracts treatment. We identified that 2 weeks of oral administration of Gouqi extracts at 10 mg/kg improved the performance of the APP/PS1 mice in the learning and the memory retrieval phases of the Morris maze. In correlation with this, the levels of Aβ(1–42) in hippocampal tissue were reduced by the Gouqi treatment. We conclude that pharmacological treatment with Gouqi extracts is beneficial at the later stages of Alzheimer’s disease.